Geographical Indications and Agri-Food Origin Labels as an Alternative for Innovation and Territorial Development (GESTIÓN Y TENDENCIAS, 2019)
The literature abounds in empirical evidence and examples in which geographical indications and agri-food origin labels serve as alternatives for innovation and territorial development. However, establishing a geographical indication or origin label does not on its own guarantee the development of innovations, the development of a territory, or the quality of life of its inhabitants and stakeholders. Such efforts must rest on a robust product-territory differentiation strategy, one that takes account of territorial dynamics. The factors relating to these dynamics must valorize and strengthen local collective action capabilities as a central element of the strategy to be developed, since those capabilities are indispensable for the proper management and use of the label, and a necessary condition for achieving commercial success and sustainability over time.